Demonstration of a high-intensity neutron source based on a liquid-lithium target for Accelerator based Boron Neutron Capture Therapy. (December 2015) - Halfon, S.; Arenshtam, A.; Kijel, D.; Paul, M.; Weissman, L.; Berkovits, D.; Eliyahu, I.; Feinberg, G.; Kreisel, A.; Mardor, I.; Shimel, G.; Shor, A.; et al.
Abstract: A free surface liquid-lithium jet target is operating routinely at Soreq Applied Research Accelerator Facility (SARAF), bombarded with a ~1.91 MeV, ~1.2 mA continuous-wave narrow proton beam. The experiments demonstrate the liquid lithium target (LiLiT) capability to constitute an intense source of epithermal neutrons, for Accelerator based Boron Neutron Capture Therapy (BNCT). The target dissipates extremely high ion beam power densities (>3 kW/cm 2, >0.5 MW/cm 3 ) for long periods of time, while maintaining stable conditions and localized residual activity. LiLiT generates ~3×10 10  n/s, which is more than one order of magnitude larger than conventional 7 Li( p, n )-based near threshold neutron sources. A shield and moderator assembly for BNCT, with LiLiT irradiated with protons at 1.91 MeV, was designed based on Monte Carlo (MCNP) simulations of BNCT-doses produced in a phantom. According to these simulations it was found that a ~15 mA near threshold proton current will apply the therapeutic doses in ~1 h treatment duration. According to our present results, such high current beams can be dissipated in a liquid-lithium target, hence the target design is readily applicable for accelerator-based BNCT. Highlights: A liquid lithium target (LiLiT) is bombarded with a 1.91 MeV, 1.5 mA CW 10 mm-wide proton beam. The target dissipates >3 kW/cm 2, >0.5 MW/cm 3 and generates ~3×10 10 n/s in stable conditions. We estimate that ~15 mA near threshold proton current would deliver therapeutic doses in ~1 h. The liquid lithium target makes in-hospital accelerator-based BNCT within reach.